The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1159/000092937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fluorodeoxyglucose Positron Emission Tomography Imaging in Metastatic Transitional Cell Carcinoma with and without Prior Chemotherapy

Abstract: Introduction: This study was designed to determine the value of fluorodeoxyglucose (FDG) positron emission tomography (PET) in the evaluation of metastatic transitional cell carcinoma (TCC). Methods: Fifty-eight FDG PET scans were performed on 46 consecutive patients with TCC. Results were correlated with radiologic, pathologic, and histologic findings in these patients and the sensitivity of PET for detecting malignancy in untreated TCC patients (n = 48) was compared to the sensitivity in patients who had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 39 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…Kibel et al, and Goodfellow et al (174)(175)(176)(177), noted sensitivity rates ranging from 60 to 77% § when using protocols for PET/ CT imaging and analyses similar to those employed in our study. We also found that sensitivity decreased from 41% on a patient level to 25% on a regional LN level, which agrees with Drieskens et al, who also noted a drop in sensitivity from 60% to 50% on the regional level (35).There is no obvious explanation for this discrepancy.…”
Section: Discussionsupporting
confidence: 66%
“…Kibel et al, and Goodfellow et al (174)(175)(176)(177), noted sensitivity rates ranging from 60 to 77% § when using protocols for PET/ CT imaging and analyses similar to those employed in our study. We also found that sensitivity decreased from 41% on a patient level to 25% on a regional LN level, which agrees with Drieskens et al, who also noted a drop in sensitivity from 60% to 50% on the regional level (35).There is no obvious explanation for this discrepancy.…”
Section: Discussionsupporting
confidence: 66%
“…It has been shown that PET/CT staging with 18 F-FDG is significantly more accurate than PET alone, and side-by-side PET and CT [19]. Several of the 18 F-FDG PET/CT studies in bladder cancer were performed with PET alone [10,16,[20][21][22][23]. In the present study combined 18 F-FDG PET/CT scans were performed in all of the patients.…”
Section: Discussionmentioning
confidence: 86%
“…Current imaging modalities like computed tomography and magnetic resonance imaging are not sensitive and/or specific. While 18F-FDG-PET has been tested in clinic for staging purposes of bladder cancer, it has not been extensively used in clinic because the sensitivity and specificity are not satisfactory [19,20]. We have shown that by linking to NIRF dye Cy5.5, PLZ4 can be used for detection of subcutaneous tumor xenograft similar to metastatic bladder cancer (Fig.…”
Section: Discussionmentioning
confidence: 99%